Tele-Affiliation in Medical Education: Experience from the International Program at Yale Office of Telemedicine - Condos, S. G.; Stamkopoulos, T.; Selles, J. M.; Merrell, R. C. (Methods of Information in Medicine, 2002)
Objectives: Telemedicine is developed in response to the needs of users that results in a more viable model. Yale has developed a process called tele-affiliation to combine services that are customized to the international client’s needs.Methods: Several defined steps compose the tele-affiliation process. The Yale-Greece telemedicine program is used as an illustration of this process. Some of the programs developed in response to Greek needs include breast cancer clinics, women’s health clinics and tele-homecare monitoring for post-operative and chronically ill patients.Results: Tele-affiliation creates an infrastructure that has the potential to change the method of health care delivery. By using the infrastructure created by the tele-affiliation process, templates for disease management, as well as health promotion and education can be delivered to a global audience.Conclusions: A tele-affiliation education environment has been developed and tested between Yale University School of Medicine and Greece resulting in an improved infrastructure for health education and management.
Keywords: Telemedicine; tele-affiliation; distance learning; training